2019
DOI: 10.1038/s41598-018-38268-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prebiotic fortified infant formulas on microbiota composition and dynamics in early life

Abstract: Gastrointestinal (GI) microbiota composition differs between breastfed and formula-fed infants. Today’s infant formulas are often fortified with prebiotics to better mimic properties of human milk with respect to its effect on GI microbiota composition and function. We used Illumina HiSeq sequencing of PCR-amplified 16S rRNA gene fragments to investigate the composition of faecal microbiota in 2–12 week old infants receiving either breastmilk, infant formulas fortified with prebiotics, or mixed feeding. We com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
62
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 61 publications
(66 reference statements)
6
62
0
3
Order By: Relevance
“…Thus, we aimed to determine whether S. mutans grows on HMOs and other prebiotics, such as GOS, which are also added to infant formulas. 2 0 -FL has been studied in infant formula at 0•2-1 g/l, for other health indications than oral health, as have GOS levels at 0•2-0•5 g/dl (5,6,9,10,33) . The 2 0 -FL concentrations that we tested exceeded those in infant formula and were slightly higher than GOS concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we aimed to determine whether S. mutans grows on HMOs and other prebiotics, such as GOS, which are also added to infant formulas. 2 0 -FL has been studied in infant formula at 0•2-1 g/l, for other health indications than oral health, as have GOS levels at 0•2-0•5 g/dl (5,6,9,10,33) . The 2 0 -FL concentrations that we tested exceeded those in infant formula and were slightly higher than GOS concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Galacto-oligosaccharides (GOS) are a mixture of lactose-based oligosaccharides with varying lengths and linkages between glucose and galactose, the terminal unit being glucose (8) . GOS are often used in infant formulas to mimic the prebiotic features of human milk (8)(9)(10) .…”
mentioning
confidence: 99%
“…They are widely distributed in a variety of plants as a storage carbohydrate [ 8 ]. Several products have been enriched with these prebiotic compounds to increase their functionality like semi-hard cheese [ 9 ], fermented sausages [ 10 ], Greek yogurt [ 11 ], fruit juices [ 12 ], infant formulas [ 13 ], and many others. Recently Brazilian ginseng ( Pfaffia glomerata ) roots were recognized as a new source of short-chain FOS, including 1-kestose, nystose, and fructofuranosylnystose with up to 8.8 g/100 g of prebiotic carbohydrates [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown similarities between the bifidogenic effect of prebiotic-fortified formulae and HBM, as compared to non-fortified formulae [59,68,69]. Indeed, prebiotics have been reported to have special effects on some bifidobacteria species such as Bifidobacterium breve.…”
Section: Prevention and Treatment Of Infant Disordersmentioning
confidence: 92%